Distributions of Dissolved Manganese in the Surface Waters of the Tropical North-Eastern Atlantic Ocean - Farah, Akmal Idrus (Universiti Malaysia Sarawak, (UNIMAS), 2016)
The tropical North-Eastern Atlantic (TNEA) Ocean region receives high atmospheric input every year, mostly from the Saharan dust and soil. This atmospheric dust and its deposition in the surface ocean are considered to be an important supply of nutrients and trace metal (e.g. dissolved manganese (DMn)) to the euphotic zone of the open ocean regions. Therefore, the objective of this study was to investigate the input of DMn from atmospheric sources and from nearby islands into the TNEA Ocean. A set of surface samples were collected from the Tropical NE Atlantic Ocean, and were analysed for DMn by using the flow injection analyser with chemiluminescence (FIA-CL). Results suggest the land-sources of DMn near to the Canary Islands, the Cape Verde Islands and the African Continent contributed the major inputs of DMn, where high DMn concentrations were determined, with the highest is 3.87±0.05 nM. The lateral advective flux of DMn was higher (47 μmol/m2/d) than the atmospheric flux of DMn (0.17 μmol/m2/d), thus making the shelf and sediment as the most prominent sources of DMn in the seawater close to the islands. From this atmospheric flux of DMn, it was then possible to estimate the DMn enrichment at further offshore dust event regions of 0.73 nM/yr and consistent with the DMn background concentrations. This support the low residence time calculated in dust event regions of around 1 year. In conclusion, the shelf and sediment are the most prominent DMn sources in the seawater close to the islands and mainland, while in further offshore, the atmospheric inputs are dominant.